REPRESENTAÇÕES E PRÁTICAS DO GINÁSIO DOM BOSCO NO SUL DO ANTIGO MATO GROSSO: EM ESTUDO O PERIÓDICO ESCOLAR O GINÁSIO (1937-1945) - JÉSSICA LIMA URBIETA (2022)
The present research aims to analyze as source and object the school periodical O Ginásio, produced and published at Ginásio Dom Bosco, in Campo Grande, south of the former Mato Grosso, from 1937 to 1945. This research is linked to the research line - Education, Culture, Society, of the Post-Graduation Program in Education, of the School of Education, of the Universidade Federal de Mato Grosso do Sul and incurses into the History and Sociology of Education. The aim is to understand the role of the periodical in the educational field, reflected by the representations contained in its pages, as well as the internal perspective of the salesian catholic educational system, based on the gymnasium practices conveyed by the printed material. As a source, it constitutes a possibility to reconstitute elements that indicate the multiple facets of the educational processes developed in the Ginásio Dom Bosco through an internal approach to the educational system. As an object, it provides specific provisions of the history and school culture of the educational environment, in which it is possible to analyze the dialogues, the denunciations, the expectations, the idealizations and the claims raised by the debates that circulated in this field between the years 1937 and 1945. The chronological delimitation of the research considered the period when the profusion of publications related to the school press by educational establishments was verified and for evidencing the editorial cycle of the periodical O Ginásio, a context that also involved a phase of intense educational debates and reordering of the educational practices with the dictatorial political regime of the Estado Novo. In the examination of the sources, we intend to engage in a dialogue with historiographic and sociological studies, based on the historical contribution of Roger Chartier and the sociological one of Pierre Bourdieu, in the condition that their studies make it possible, given the objectives and questions of the research, to understand the relationship between the school structure and its agents, referring to the production of representations and practices of the Ginásio Dom Bosco. The proposal of the thesis and the results of the research indicate that the school periodical O Ginásio brought an approach about the Salesian educational phenomenon of the Ginásio Dom Bosco from the analysis of the representations and practices conveyed in its pages, which contained, above all, indications about the various extensions of school life, the discourses that were spread in the environment and elements of the daily school life of this religious establishment. The observation of the values, customs, ideals, beliefs and interests that defined the relationships in the gymnasium and the editorial process of the publications, as well as the appropriations made by the agents from the school culture of the establishment, explain that the printed material played a strategic role in the diffusion of values and catholic way of life, because its technical, material and ideological proposals were linked to the struggles and sociopolitical perspectives of the educational field of the period. In summary, the structure of the field was based on the effectiveness of a symbolic product that acted as an ally in the defense of the preventive educational system and in the propagation of its actions, which made this enterprise a collective project committed to disseminate the interests, the representations and the practices undertaken by the Ginásio Dom Bosco.